Enhancing Algebraic Reasoning in The Classroom: The Effects of Search, Solve, Create, and Share Strategy - Mochamad Abdul Basir; Mohamad Aminudin; Dyana Wijayanti; Herlian Dessi Kusumawati (Hipotenusa: Journal of Mathematical Society, 2025)
Algebraic reasoning is a fundamental competency in mathematics learning; however, many students experience difficulties in applying algebraic concepts, particularly in quadratic functions. This study aims to enhance students’ algebraic reasoning through the implementation of the SSCS (Search, Solve, Create, and Share) strategy, a structured problem-solving instructional approach that emphasizes systematic exploration, solution development, model construction, and mathematical communication. The study employed a collaborative classroom action research design involving Grade X senior high school students, conducted across two cycles consisting of planning, action, observation, and reflection stages. Students’ algebraic reasoning was assessed using indicators that include pattern recognition, algebraic representation, manipulation of algebraic expressions, and logical justification. Data were collected through algebraic reasoning tests and classroom observation sheets. The findings reveal a substantial improvement in students’ algebraic reasoning abilities, with the mean score increasing from 62.33 in the pre-cycle to 81.25 in Cycle II. Additionally, the percentage of students achieving mastery learning increased from 27.78% to 91.67%. These results indicate that the SSCS strategy effectively supports the development of algebraic reasoning by engaging students in structured problem-solving and reflective mathematical communication.